The Rigour of IFRS Education in the USA: Analysis, Reflection and Innovativeness - Tan, Aldys; Chatterjee, Bikram; Bolt, Susan (Routledge, 2014)
International Financial Reporting Standards (IFRS) are accepted throughout the world, particularly in the European Union, Australia, New Zealand and Canada. Emerging economies are also are aligning their practices with IFRS. Historically, the USA has been cautious about accepting IFRS. However, following acceptance of IFRS worldwide, the US Securities and Exchange Commission has recently allowed the filing of IFRS-based financial statements from foreign issuers and is presently considering the same from domestic issuers. Owing to lack of IFRS education and training in the country, concerns have been expressed about such moves of the USA towards IFRS. Following such concerns, the aim of the present study is to review previous literature on IFRS education to reflect on the present status of IFRS education in the USA. The research method includes a review of past literature on IFRS education in the Business Source Complete database from 2001 to 2012.In line with the review, this study reports that active learning approaches that stimulate critical thinking and judgement skills of students are the best methods to teach IFRS. The studies reviewed also report the lack of teaching materials, including software and technologies, to effectively teach IFRS. The only active learning strategies advocated in previous studies were the use of case studies and real life examples. Additionally, this study advocates the use of problem-based learning strategies. This study also reports the lack of research investigating students’ and educators' perceptions of available resources and approaches. Future studies are suggested in this direction, employing surveys and interviews.